A Matriz Sigilar Medieval de Martim Abarca (Tavira) - Barroca, Mário Jorge (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2017)
Study of the medieval sigilar matrix of Martin Abarca, a noble man of Castilian origin. The sigilar matrix is attributable to the second half of the 13th century or the first decades of the 14th century. It appeared in a private property in the historic center of Tavira, near the Muslim walls and the Christian castle.